Economic evaluations of early detection strategies for pancreatic cancer: a systematic review - Léon Kreis; Hans-Helmut König; Christian Brettschneider (The European Journal of Health Economics, 2025)
Objectives: The early detection of pancreatic cancer is an important step in reducing mortality by offering patients curative treatment. The aim of this study was to synthesize available evidence on the costs and cost-effectiveness of strategies for early pancreatic cancer detection. Methods: The electronic databases PubMed, Web of Science, and EconLit were searched for peer-reviewed and published papers in English until April 2024 with no date or contextual restrictions. Economic evaluations of early pancreatic cancer detection strategies compared to alternative or no detection strategies were criteria for inclusion. Results: Thirty-one articles were included, 22 were full and nine were partial economic evaluations. Fifteen studies screened target populations with pancreatic cancer-associated risk factors and 16 conducted surveillance of patients with precancerous lesions. Six studies found early detection strategies to be cost-effective, one did not, and thirteen reported partially cost-effective results. In all studies, populations of interest had an elevated pancreatic cancer risk compared to the general population. Endoscopic ultrasound, magnetic resonance imaging, and computed tomography were the most frequently evaluated imaging modalities. Patient engagement, valuation of outcomes and choice of discount rates were among incomplete reporting categories, and narrow evaluation perspectives may have biased the results. Conclusions: Early detection strategies for pancreatic cancer may be cost-effective for certain high-risk patient groups. However, evaluations so far have applied heterogeneous methods, used different modalities, had various target groups and screened at different frequencies. Further evaluations will be required to systematically synthesize economic evidence regarding specific early detection strategies. Registration: PROSPERO registration CRD42023475348.
Keywords: 610; Pancreatic cancer; Early detection; Economic evaluation; Systematic review